2022
DOI: 10.1021/acs.jpca.2c05851
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Polymer Molecular Dynamics and Kinetics for the H + C2H2 → H2 + C2H Reaction Using the Full-Dimensional Potential Energy Surface

Abstract: reaction is important in understanding the production mechanisms of anionic molecules in interstellar environments. Herein, the rate coefficients for the H − + C 2 H 2 → H 2 + C 2 H − reaction were calculated using ring-polymer molecular dynamics (RPMD), classical molecular dynamics (MD), and quasi-classical trajectory (QCT) approaches on a newly developed ab initio potential energy surface (PES) in full dimensions. PES was constructed by fitting a large number of ab initio energy points and their gradients us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 70 publications
3
24
0
Order By: Relevance
“…This fitted PES was used to identify unphysical leaky holes on the PES. Previous studies reported that leaky holes frequently occur around nuclear configurations that have not been explored using GRRM or random sampling. , To identify such leaky holes, we performed extensive classical trajectory calculations starting from various structures. When an unphysical hole was found, additional sampling around the hole was performed to remove the unphysical hole.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…This fitted PES was used to identify unphysical leaky holes on the PES. Previous studies reported that leaky holes frequently occur around nuclear configurations that have not been explored using GRRM or random sampling. , To identify such leaky holes, we performed extensive classical trajectory calculations starting from various structures. When an unphysical hole was found, additional sampling around the hole was performed to remove the unphysical hole.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…The method has been widely utilized and has successfully described chemical reactions such as collision processes in the gas phase and diffusion processes in the condensed phase. [12,[25][26][27][28][29][30][31][32][33][34][35] Our RPMD method employs the direct trajectory technique, which is similar to the dRPMD program [36] implemented in RPMDrate code. [37] For our RPMD approach, we performed thermalization and implemented real-time dynamics on the open-source PIMD Ver.…”
Section: Rpmdmentioning
confidence: 99%
“…Further details of the collision procedure have been presented in our previous H 2 + (H 2 O) 8 , H 3 + + CO, and H À + C 2 H 2 studies. [12,34,35] Classical MD simulations were also performed in essentially the same way as the PIMD/RPMD calculations mentioned above. The classical Hamiltonian H p;r ð Þ has the conventional form for the n-atom system:…”
Section: Rpmdmentioning
confidence: 99%
See 2 more Smart Citations